The Measurement of Managerial Efficiency Changes of Dairy Cooperatives in Saraburi Province, Thailand based on The Malmquist Data Envelopment Analysis Approach - Wittayakorn-Puripunpinyoo, Anucha (Asia Social Issues, 2025)
The research objectives were to measure: 1) the technical efficiency change (TEC) relative to Constant Return to Scale (CRS) technology of the dairy cooperative in Saraburi province, 2) the technological change (TC), 3) pure technical efficiency (PTE) change relative to a Vary Return to Scale (VRS) and 4) the scale efficiency (SE) change of cooperative. The research was a quantitative research. The secondary data were collected from the Cooperatives Auditing Department from 2013 to 2022. The data were collected from the entire population using electronic spreadsheets. The findings were: 1) the TEC relative to the CRS had an average score of 1.000, expressing the cooperatives had no TEC; 2) the average score of TC was equal to 0.995, expressing their decreasing of TC; 3) the average score of pure efficiency change of cooperative was equal to 1.000 expressing the increased managerial technique of operational performances, and 4) the average score of the total factor of productivity change was equal to 0.996 expressed the decreased total factor of productivity change. It was concluded that dairy cooperatives had no TEC change. The pure efficiency change of dairy cooperatives expressed the increased managerial technique of their operational performances. In contrast, their score for the total factor of productivity change expressed the decreased total factor of productivity change of dairy cooperatives. The findings suggested that the modern dairy farming and dairy cooperatives are constantly searching for innovations to increase milk yields, enhance milk quality, and reduce costs.